Comprehensive analysis of Twitter activity on #Incontinence. Issue 1 (20th November 2019) - Grabbert, Markus; Khoder, Wael Y.; Gratzke, Christian; Paffenholz, Pia; Salem, Johannes; Bauer, Ricarda M.
Abstract: Aim: The aim of this study is comprehensive analysis of the Twitter activity on #Incontinence. Material and Methods: The following six functional‐urology hashtags on Twitter were analyzed from 2015 to 2018 to gain a comprehensive insight into the topic: #Incontinence, #InterstitialCystitis, #OAB, #FPMRS, #BPH, and #UroBPH. For the Twitter analysis, Symplur Signals was used, which is a health care social media analytics tool. Results: In total 191 383 tweets by 54 094 users in 2015 through 2018 were analyzed. A rise in the number of tweets could be identified for all six analyzed hashtags on functional urology, in summary, the numbers raised from 25 629 tweets in 2015 to 66 551 tweets in 2018. For the hashtag incontinence (#Incontinence), the number of tweets raised from 13 823 in 2015 to 19 996 in 2018 (+44.7%). Main influencers on functional urology topics identified by the Symplur algorithm were individuals from the health care sector in 44.6% of the cases and health care organizations in 36.5% of the cases, whereas for #Incontinence, only 7% of influencers were patients in 2018. The ten most common words connected to #Incontinence were Incontinence, Urinary, Women, Help, New, Bladder, Stress, Treatment, Pelvic, and Sex . Of the tweets, 66% were categorized as positive statements and 34% were categorized as negative. Conclusion: Social media is an emerging tool of communication in urology, whereas discussions on #Incontinence are underrepresented compared to the high prevalence of urinary incontinence. In addition, patients' activity is low.